Publisher Correction: Hydrogen-rich supernovae beyond the neutrino-driven core-collapse paradigm. (February 2018) - Terreran, G.; Pumo, M.; Chen, T.-W.; Moriya, T.; Taddia, F.; Dessart, L.; Zampieri, L.; Smartt, S.; Benetti, S.; Inserra, C.; Cappellaro, E.; Nicholl, M.; et al.
In the version of this Article originally published the Fig. 6 y axis label read 'Mej' but should have read 'MNi'. This has now been corrected.